Genome assembly and visualization of aggressive wheat blast strain 16MoT01 - Burke, Eva; Bika, Ravi; Lin, Guifang; Liu, Sanzhen (My University, 2022)
Wheat blast, a highly destructive fungal disease caused by pathotype Magnaporthe oryzae Triticum, can cause up to 100% yield loss in wheat fields under optimal pathogen conditions. Until 2016, the disease had been confined to South America, but recent outbreaks of the disease in Asia and Africa threaten the global wheat supply. This study aims to characterize the genome structure of strain 16MoT01, which has proven to be particularly aggressive even towards wheat genotypes that have previously been resistant to blast. Genomic DNA from 16MoT01 was sequenced using Oxford Nanopore long read sequencing, assembled with Canu, and polished using Illumina reads, resulting in a finished chromosome-level assembly consisting of seven core-chromosomes, a mini-chromosome, and a mitochondrial genome. When compared to the reference genome of strain B71, the core-chromosomes show high similarity and the mini-chromosome shows a high level of divergence. The presence of mini-chromosomes will be confirmed through contour-clamped electric field (CHEF) gel electrophoresis. The CHEF protocol was developed using genomic DNA from a rice blast fungus. This assembly provides another reference genome and potential insights into what makes this strain so aggressive.
Keywords: plant pathology; wheat blast; Magnaporthe; Oxford Nanopore; mini-chromosome; USDA NIFA 2019-67032-29071